2019
DOI: 10.1002/mp.13423
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering for dosimetry using GAFCHROMIC EBT3 radiochromic dosimetry film

Abstract: Purpose: Raman scattering spectra can be thought of as the "fingerprints" of the investigated material. The purpose of this work was to link the absorbed doses of irradiated radiochromic film at the micrometer level with changes in their Raman spectra. Methods: Raman spectra of irradiated GAFCHROMIC EBT3 film with doses ranging from 0 to 40 Gy were acquired. The excitation wavelengths used in the experiments (457.9 and 647.1 nm) coincided with electronic transitions of the active layer of the film. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Over the last few decades, different types of radiochromic films with a resolution of fewer than 100 µm have been investigated using an optical scanner or a densitometer, as explained in more detail elsewhere . The spectral response of radiochromic films has been explored to find out new and improved readout systems for high‐spatial resolution dosimetry . In the previous study, we developed a novel Raman mapping technique to measure the variation in Raman spectra of carbon double (C = C) and triple (C≡C) stretching bands of diacetylene polymer as a function of therapeutic x‐ray doses with a high‐spatial resolution .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few decades, different types of radiochromic films with a resolution of fewer than 100 µm have been investigated using an optical scanner or a densitometer, as explained in more detail elsewhere . The spectral response of radiochromic films has been explored to find out new and improved readout systems for high‐spatial resolution dosimetry . In the previous study, we developed a novel Raman mapping technique to measure the variation in Raman spectra of carbon double (C = C) and triple (C≡C) stretching bands of diacetylene polymer as a function of therapeutic x‐ray doses with a high‐spatial resolution .…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, we developed a novel Raman mapping technique to measure the variation in Raman spectra of carbon double (C = C) and triple (C≡C) stretching bands of diacetylene polymer as a function of therapeutic x‐ray doses with a high‐spatial resolution . Recently, Talarico et al performed a similar Raman mapping technique on EBT3 film with a 40‐µm spatial resolution and observed that the ratio of the peak intensities of C = C stretching mode around 1450 cm −1 and CH 2 vibrations around 1330 cm −1 grows with the increase in radiation dose . Reading out with Raman spectroscopy was advantageous in the sense that any delicate chemical changes caused by radiation can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Dosimeters such as ionization chambers, films, thermoluminescent dosimeter (TLD), metal oxide semiconductor field‐effect transistor (MOSFET)‐based devices, and silicon diode detectors have been developed for this purpose. However, they often fall short of energy dependence, tissue equivalence, or spatial resolution 1,2,3 . In particular, measuring the dose distribution at the micrometer scale has been a challenge in radiation dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, radiochromic films are examined through optical densitometers to measure shifts in their optical density for different doses. Recent studies have used Raman spectroscopy to determine the compositional changes in the radiochromic film structure due to the polymerization of LiPCDA monomers 1.4–8 . Due to such favorable characteristics, RCF has been widely used for dose measurements in radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation